PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA BERVISI SETS DENGAN METODE DISCOVERY LEARNING UNTUK MENANAMKAN NILAI BAGI SISWA SEKOLAH DASAR - Setyo Eko Atmojo (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2015)
This study aims to develop the vision SETS elementary science learning with discovery learning method. To know effectivity elementary science teaching tools in growing SETS visionary science process skills and instill values in themselves and to know the implementation learning devices in the classroom. This study is a research & development (R & D / Research and Development) is a software product developed science learning in Fifth Grade Elementary School envisions SETS with discovery learning method. Based on the results of analysis show the validity of the learning value is 4.12 on a valid category. Average student has good science process skills, the average percentage of the value of > 70 %, the effective development of learning tools for to build values in students. Average student learning outcomes in the category of either > 70, the development of learning outcomes appropriate to apply > 80 % of students gave positive responses. SETS visionary science learning by discovery learning methods to actively engage students in learning, can improve science process skills, instill values in students, and provide an average of student learning outcomes that achieve average scores > 70. Implementation LKS and LDS assist students in learning, apply science concepts and provide opportunities for students to apply as scientists so as to provide a more in-depth experience of the concept of science.